2000
DOI: 10.4049/jimmunol.164.7.3563
|View full text |Cite
|
Sign up to set email alerts
|

IL-4, IL-10, IL-13, and TGF-β from an Altered Peptide Ligand-Specific Th2 Cell Clone Down-Regulate Adoptive Transfer of Experimental Autoimmune Encephalomyelitis

Abstract: Experimental autoimmune encephalomyelitis (EAE) is induced in the SJL/J mouse by adoptive transfer of activated proteolipid protein peptide (PLP) 139-151-specific Th1 cells. T cells responding to altered peptide ligands (APL) of PLP, previously shown to induce Th2 differentiation and regulate disease in PLP-immunized mice, do not transfer EAE. However, the exact mechanism of disease regulation by APL-specific T cells has not been elucidated. In this report, we show that 1F1, a Th2 clone specific for an APL of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 53 publications
3
90
0
Order By: Relevance
“…Its role in EAE has been of an anti-inflammatory cytokine. Young et al (21) showed that IL-13 inhibited the adoptive transfer of proteolipid protein-induced EAE in female SJL mice, and our previous study demonstrated increased levels of IL-13 in SJL mice after successful treatment of passive EAE with a rTCR ligand (22). Our unexpected observation that female IL-13KO mice have a lower incidence and reduced severity of EAE than males, prompted us to compare gender differences of immune cells from these mice.…”
Section: Discussionmentioning
confidence: 86%
“…Its role in EAE has been of an anti-inflammatory cytokine. Young et al (21) showed that IL-13 inhibited the adoptive transfer of proteolipid protein-induced EAE in female SJL mice, and our previous study demonstrated increased levels of IL-13 in SJL mice after successful treatment of passive EAE with a rTCR ligand (22). Our unexpected observation that female IL-13KO mice have a lower incidence and reduced severity of EAE than males, prompted us to compare gender differences of immune cells from these mice.…”
Section: Discussionmentioning
confidence: 86%
“…It should be noted that although NKT cells have been frequently associated with Th2 responses (61,62), depletion of only NK cells can affect IgE (63) as well as IgG1 responses under specific conditions of immunization (2). In addition, although IL-13 has generally been associated with allergic inflammation (45), the cytokine may also play a role in other diseases as well (64). It remains to be shown whether the B cell induction of IL-13 expression by NK cells plays a significant role in these responses.…”
Section: Discussionmentioning
confidence: 99%
“…Autoantigen-reactive Th2 cells have mostly been associated with protection from autoimmune disease (32)(33)(34). However, it has recently been shown that Th2 cells can mediate autoimmune pathology in some models (35,36).…”
Section: Ifa-induced Plpp139 -151-specific Th2 Cells Are Not Renderedmentioning
confidence: 99%